2012
DOI: 10.1038/nature11017
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of cancer genes and mutational processes in breast cancer

Abstract: All cancers carry somatic mutations in their genomes. A subset, known as driver mutations, confer clonal selective advantage on cancer cells and are causally implicated in oncogenesis1, and the remainder are passenger mutations. The driver mutations and mutational processes operative in breast cancer have not yet been comprehensively explored. Here we examine the genomes of 100 tumours for somatic copy number changes and mutations in the coding exons of protein-coding genes. The number of somatic mutations var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

66
1,307
7
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,519 publications
(1,417 citation statements)
references
References 32 publications
66
1,307
7
11
Order By: Relevance
“…Activating PIK3CA point mutations are among the most common genetic aberrations in invasive breast cancer, [1][2][3][4][5][6][7][8][9][10] and several studies have shown that these mutations exist at nearly the same frequency in DCIS. [14][15][16][17] Accumulating evidence suggests that PIK3CA point mutations may also be common in other proliferative breast lesions such as benign papillomas and columnar cell lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Activating PIK3CA point mutations are among the most common genetic aberrations in invasive breast cancer, [1][2][3][4][5][6][7][8][9][10] and several studies have shown that these mutations exist at nearly the same frequency in DCIS. [14][15][16][17] Accumulating evidence suggests that PIK3CA point mutations may also be common in other proliferative breast lesions such as benign papillomas and columnar cell lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Our data on PIK3CA mutations in DCIS (48% in this study and 45% combined) and invasive mammary carcinoma (35% in this study and 34% combined) matches the literature. [1][2][3][4][5][6][7][8] We identified point mutations in other genes in invasive carcinomas, but not in 'earlier' lesions, including TP53, FBXW7, FGFR2, and HRAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical evidence is compelling for histologic progression of breast cancer through atypical hyperplasia, ductal carcinoma in situ (DCIS), invasive ductal carcinoma, and metastatic stages. 1 Such histopathologic progression studies and mutational profiling of epithelial cancers 2,3 suggest that acquisition of invasive potential is a relatively late event. However, genomic data analyses have revealed that most tumor cell gene expression changes occur at the transition from normal to DCIS, with few additional changes in expression occurring at the transition from DCIS to overt invasive disease.…”
mentioning
confidence: 99%